Cowboys and Bohemians: Recreation, Resistance, and the Tramping Movement in West Bohemia - Symonds, James; Vařeka, Pavel (Journal of Contemporary Archaeology, 2014)
In this paper we examine a prominent but little studied aspect of everyday life in Central Europe, the Czech tramping movement. We aim to show how workers and students from Czech industrial towns and cities created and sustained imaginary rural spaces and flamboyant alternative personas. In some cases these shared fantasy worlds were understood to be a simple leisure pursuit. In other instances tramping activity was a form of resistance and provided a means of escape from the monotony of everyday life, and political repression by the Communist authorities.